Hadis dan Ilmu Hadis dalam Pandangan Ahl al-Sunnah dan Syiah - Jumal Ahmad (Qur'an and Hadith Academic Society, 2017)
This study focused on hadith and the science of hadith in the view of Ahlus Sunnah and Shia. Ahl al-Sunnah and Shia view the hadith as a source of Islam. The existence of different cultural roots of each group makes the Hadith can not be separated from the interests of group authority. The Shi'a believe that the revelation did not stop after the death of the Prophet Muhammad. In the verification of the hadith, the Shi'ah provided the criteria for the existence of a continuation of the ma'shum and all the narrators in the sanad came from the Shi'a group at all levels.